Pengaruh Penyajian Laporan Pertanggungjawaban Dan Aksesibilitas Terhadap Transparansi Dan Akuntabilitas Pengelolaan Dana Di Desa Sialang Rindang Kecamatan Tambusai Kabupaten Rokan Hulu - Sarah Hasibuan; Nurhayati (Fakultas Ekonomi Universitas Pasir Pengaraian, 2020)
This study aims to determine the effect of the presentation of accountability and accessibility reports on transparency and accountability of village fund management in Sialang Rindang village, Tambusai district, Rokan Hulu district. The research method used is quantitative research methods. The population in this study were all RT, RW, Hamlet, BPD, LPMD, and BUMDES Sialang Rindang village, Tambusai district, Rokan Hulu regency as many as 60 respondents. The analysis technique used in this study is multiple linear regression analysis techniques which funchtion to determine the linear relationship between two or more variables. The results of the study the influence of the presentation of the accountability report on transparency of tcount 4,104 > ttable 2,00172. accessibility to transparency is 3,781 > ttable 2,00172. The report of accountability to accountability of tcount 4,511> ttable 2,00172. Accessibility to accountability of tcont 3,311 > ttable 2,00172. ttest results show that partially there is an influence between the independent and dependen variables. While the F test result are dependen variable transparancy, the value of Fcount> Ftable (36.075 > 3.156) with a significance level of 0.000 <0.05 and the Ftest results of the dependent variable accountability, Fcount > Ftable (35.709 > 3.156) with a significance level of 0.000 < 0.05, Ha is accepted, the calculation shows that the simultaneous presentation of accountability and accessibility reports influnces the transparency and accountability of village fund managemen.